Penggunaan media permainan ular tangga untuk meningkatkan hasil belajar pada materi ekologi di kelas VII SMP Negeri 3 Balaraja - Muliyani, Heny; Ani Nikmah; Faruq Haroky; Rizqi Nur Rachmawati; Fitri Rizkiyah (Jurnal Kajian Pendidikan IPA, 2025)
This study aims to investigate the effect of using the "Snakes and Ladders" game as an instructional medium on improving students’ learning outcomes in the Ecology material among seventh- grade students at SMP Negeri 3 Balaraja. The research was motivated by the low academic achievement of students, which was attributed to the use of less engaging teaching media and monotonous instructional methods. A Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model was employed, implemented over three cycles, involving a total of 40 students as research subjects. Data were collected through observation and testing methods, including pre-tests and post-tests. The findings revealed a significant improvement in students’ learning outcomes, with average scores increasing from 47% in the first cycle to 64% in the second cycle, and reaching 83% in the third cycle. The mastery level also improved substantially, from 10% to 95%. Statistical analysis using the paired sample t-test yielded a significance value of p < 0.05, indicating a statistically significant impact of the "Snakes and Ladders" game-based media on students’ academic performance. Therefore, the use of this interactive game medium is proven to be effective in enhancing students’ learning outcomes and promoting active participation in Ecology lessons. Keywords: Snakes and ladders game, Instructional media, Ecology, Learning outcomes